To solve this problem, we'll distribute the fractions and combine like terms:
1/2(x+4)+1/4(4x−2)
=(1/2)x+2+1/4(4x)−1/4(2)
=(1/2)x+2+(4/4)x−(2/4)
=(1/2)x+(4/4)x+2−2/4
=(1/2)x+(1)x+1/2
=(1/2)x+(2/2)x+1/2
=(3/2)x+1/2
Now, we can write the answer in mixed number form:
3/2x + 1/2 = 1 1/2x + 1/2
Add: 1/2(x+4)+1/4(4x−2) . Answer should be in mixed number form.(1 point)
37 answers
Add: (2m−3)+(3n−1)+(3m+1
To solve this problem, we need to combine like terms:
(2m - 3) + (3n - 1) + (3m + 1)
= 2m - 3 + 3n - 1 + 3m + 1
= (2m + 3m) + (-3 - 1 + 1) + (3n)
= 5m - 3 + 3n
= 5m + 3n - 3
Therefore, the answer is 5m + 3n - 3.
(2m - 3) + (3n - 1) + (3m + 1)
= 2m - 3 + 3n - 1 + 3m + 1
= (2m + 3m) + (-3 - 1 + 1) + (3n)
= 5m - 3 + 3n
= 5m + 3n - 3
Therefore, the answer is 5m + 3n - 3.
Subtract: 2(10b+4)−(b−2)
To subtract, we need to distribute the 2 first, and then simplify:
2(10b + 4) - (b - 2)
= 20b + 8 - (b - 2)
= 20b + 8 - b + 2
= 19b + 10
Therefore, the answer is 19b + 10.
2(10b + 4) - (b - 2)
= 20b + 8 - (b - 2)
= 20b + 8 - b + 2
= 19b + 10
Therefore, the answer is 19b + 10.
Subtract: (3g−4)−2(3g+4) .
To subtract, we need to distribute the -2 first, and then simplify:
(3g - 4) - 2(3g + 4)
= 3g - 4 - 2(3g) - 2(4)
= 3g - 4 - 6g - 8
Now, we can combine like terms:
= (3g - 6g) + (-4 - 8)
= -3g - 12
Therefore, the answer is -3g - 12.
(3g - 4) - 2(3g + 4)
= 3g - 4 - 2(3g) - 2(4)
= 3g - 4 - 6g - 8
Now, we can combine like terms:
= (3g - 6g) + (-4 - 8)
= -3g - 12
Therefore, the answer is -3g - 12.
(k+13/)+10(1/2k−1)
To solve this expression, we will distribute 10 to the terms inside the parentheses and simplify:
(k + 13/) + 10(1/2k - 1)
= k + 13/ + 10(1/2k) - 10(1)
= k + 13/ + (10/2)k - 10
= k + 13/ + 5k - 10
Now, we combine like terms:
= k + 5k + 13/ - 10
= 6k + 13/ - 10
To get a common denominator for the fractions, we multiply 10 by 2/2:
= 6k + 13/ - 20/2
= 6k + 13/ - 10
Therefore, the final answer is 6k + 13/ - 10.
(k + 13/) + 10(1/2k - 1)
= k + 13/ + 10(1/2k) - 10(1)
= k + 13/ + (10/2)k - 10
= k + 13/ + 5k - 10
Now, we combine like terms:
= k + 5k + 13/ - 10
= 6k + 13/ - 10
To get a common denominator for the fractions, we multiply 10 by 2/2:
= 6k + 13/ - 20/2
= 6k + 13/ - 10
Therefore, the final answer is 6k + 13/ - 10.
9(k+13/)+10(1/2k−1)
To solve this expression, we'll first distribute the 9 and the 10 to the terms inside the parentheses and simplify:
9(k + 13/) + 10(1/2k - 1)
= 9k + 9(13/) + 10(1/2k) - 10(1)
= 9k + (9*13/) + (10/2)k - 10
= 9k + 117/ + 5k - 10
Now, we combine like terms:
= 9k + 5k + 117/ - 10
= 14k + 117/ - 10
To get a common denominator for the fraction, we multiply 10 by 2/2:
= 14k + 117/ - 20/2
= 14k + 117/ - 10
Therefore, the final answer is 14k + 117/ - 10.
9(k + 13/) + 10(1/2k - 1)
= 9k + 9(13/) + 10(1/2k) - 10(1)
= 9k + (9*13/) + (10/2)k - 10
= 9k + 117/ + 5k - 10
Now, we combine like terms:
= 9k + 5k + 117/ - 10
= 14k + 117/ - 10
To get a common denominator for the fraction, we multiply 10 by 2/2:
= 14k + 117/ - 20/2
= 14k + 117/ - 10
Therefore, the final answer is 14k + 117/ - 10.
9(k+13/)+10(1/2k−1)
14k−2/3
14 k minus Start Fraction 2 over 3 End Fraction
1912k−2/3
19 Start Fraction 1 over 2 End Fraction k minus Start Fraction 2 over 3 End Fraction
14k−7
14 k minus 7
14k+13
14k−2/3
14 k minus Start Fraction 2 over 3 End Fraction
1912k−2/3
19 Start Fraction 1 over 2 End Fraction k minus Start Fraction 2 over 3 End Fraction
14k−7
14 k minus 7
14k+13
Apologies for the confusion in the previous responses. Let's proceed with the updated expression:
9(k + 13/) + 10(1/2k - 1)
= 9k + 9(13/) + 10(1/2k) - 10(1)
= 9k + 117/ + 5/2k - 10
To combine like terms, we need to get a common denominator for the fractions. We can multiply 10 by 2/2 to achieve this:
= 9k + 117/ + (5/2k)*(2/2) - (10)*(2/2)
= 9k + 117/ + 10/2k - 20/2
= 9k + 117/ + 10/2k - 10
Now, we can further simplify by finding a common denominator for the fractions in the expression:
= 9k + 117/ + 5k/ + 10/2k - 10
= 9k + 117/ + 5k/2 + 10/2k - 10
Now, let's combine all the terms:
= 9k + 5k/2 + 117/ + 10/2k - 10
To add the fractions, we need a common denominator. Multiply 10 by 2/2:
= 9k + 5k/2 + 117/ + 10/2k - 20/2
= 9k + 5k/2 + 117/ + 10/2k - 20/2
= 9k + 5k/2 + 117/ - 20/2 + 10/2k
= 9k + 5k/2 + 117/2 - 10/2k
To simplify the expression further, we need to find a common denominator for the mixed numbers 5k/2 and 117/2:
= 9k + (5k/2)*(2/2) + (117/2)*(k/2k) - (10/2k)*(117/117)
= 9k + 10k/2 + 117k/2k - 10k/117
= 9k + 20k/2 - 10k/117
= 9k + 10k - 10k/117
= 9k
Therefore, the final answer is 9k.
9(k + 13/) + 10(1/2k - 1)
= 9k + 9(13/) + 10(1/2k) - 10(1)
= 9k + 117/ + 5/2k - 10
To combine like terms, we need to get a common denominator for the fractions. We can multiply 10 by 2/2 to achieve this:
= 9k + 117/ + (5/2k)*(2/2) - (10)*(2/2)
= 9k + 117/ + 10/2k - 20/2
= 9k + 117/ + 10/2k - 10
Now, we can further simplify by finding a common denominator for the fractions in the expression:
= 9k + 117/ + 5k/ + 10/2k - 10
= 9k + 117/ + 5k/2 + 10/2k - 10
Now, let's combine all the terms:
= 9k + 5k/2 + 117/ + 10/2k - 10
To add the fractions, we need a common denominator. Multiply 10 by 2/2:
= 9k + 5k/2 + 117/ + 10/2k - 20/2
= 9k + 5k/2 + 117/ + 10/2k - 20/2
= 9k + 5k/2 + 117/ - 20/2 + 10/2k
= 9k + 5k/2 + 117/2 - 10/2k
To simplify the expression further, we need to find a common denominator for the mixed numbers 5k/2 and 117/2:
= 9k + (5k/2)*(2/2) + (117/2)*(k/2k) - (10/2k)*(117/117)
= 9k + 10k/2 + 117k/2k - 10k/117
= 9k + 20k/2 - 10k/117
= 9k + 10k - 10k/117
= 9k
Therefore, the final answer is 9k.
Use the properties of operations to add 4(g−2)+(g+2) .(1 point)
Responses
5g−10
5 g minus 10
5g
5 g
5g+10
5 g plus 10
5g−6
Responses
5g−10
5 g minus 10
5g
5 g
5g+10
5 g plus 10
5g−6
To add 4(g - 2) + (g + 2), we'll distribute the 4 and combine like terms:
4(g - 2) + (g + 2)
= 4g - 8 + g + 2
Combining like terms:
= 4g + g - 8 + 2
= 5g - 6
Therefore, the answer is 5g - 6.
4(g - 2) + (g + 2)
= 4g - 8 + g + 2
Combining like terms:
= 4g + g - 8 + 2
= 5g - 6
Therefore, the answer is 5g - 6.
Use the properties of operations to subtract (h+k)−(2k−h) .(1 point)
Responses
2h−k
2 h minus k
2h+k
2 h plus k
−2h−k
negative 2 h minus k
−k
Responses
2h−k
2 h minus k
2h+k
2 h plus k
−2h−k
negative 2 h minus k
−k
To subtract (h + k) - (2k - h), we'll distribute the negative sign and combine like terms:
(h + k) - (2k - h)
= h + k - 2k + h
Combining like terms:
= h + h + k - 2k
= 2h - k
Therefore, the answer is 2h - k.
(h + k) - (2k - h)
= h + k - 2k + h
Combining like terms:
= h + h + k - 2k
= 2h - k
Therefore, the answer is 2h - k.
(p−3)−(2.4+2p) .(1 point)
Responses
p−5.4
p minus 5.4
−p+5.4
negative p plus 5.4
−p−5.4
negative p minus 5.4
3p−5.4
Responses
p−5.4
p minus 5.4
−p+5.4
negative p plus 5.4
−p−5.4
negative p minus 5.4
3p−5.4
To subtract (p - 3) - (2.4 + 2p), we'll distribute the negative sign and combine like terms:
(p - 3) - (2.4 + 2p)
= p - 3 - 2.4 - 2p
Combine like terms:
= p - 2p - 3 - 2.4
= -p - 2.4 - 3
= -p - 5.4
Therefore, the answer is -p - 5.4.
(p - 3) - (2.4 + 2p)
= p - 3 - 2.4 - 2p
Combine like terms:
= p - 2p - 3 - 2.4
= -p - 2.4 - 3
= -p - 5.4
Therefore, the answer is -p - 5.4.
Subtract: 2(k−4)−3(2k−1) .(1 point)
Responses
−4k−11
negative 4 k minus 11
8k−11
8 k minus 11
−4k−5
negative 4 k minus 5
−6k−18
Responses
−4k−11
negative 4 k minus 11
8k−11
8 k minus 11
−4k−5
negative 4 k minus 5
−6k−18
To subtract 2(k - 4) - 3(2k - 1), we'll distribute the 2 and 3 and combine like terms:
2(k - 4) - 3(2k - 1)
= 2k - 8 - 6k + 3
Combine like terms:
= (2k - 6k) + (-8 + 3)
= -4k - 5
Therefore, the answer is -4k - 5.
2(k - 4) - 3(2k - 1)
= 2k - 8 - 6k + 3
Combine like terms:
= (2k - 6k) + (-8 + 3)
= -4k - 5
Therefore, the answer is -4k - 5.
1/2 (x + 4) + 1/4 (4x + 2)
To solve this problem, we'll distribute the fractions and combine like terms:
1/2 (x + 4) + 1/4 (4x + 2)
= (1/2)x + 2 + (1/4)(4x) + (1/4)(2)
= (1/2)x + 2 + 4/4x + 2/4
= (1/2)x + 2 + x + 1/2
= (1/2)x + x + 2 + 1/2
To add the fractions, we need a common denominator. Multiply 2 by 2/2:
= (1/2)x + (2/2)x + 2 + 1/2
= (1/2)x + (2/2)x + 2 + 1/2
= (1/2 + 2/2)x + 2 + 1/2
= (3/2)x + 2 + 1/2
Now, we can write the answer in mixed number form:
= (3/2)x + 2 + 1/2
= (3/2)x + 2 + 1/2
= (3/2)x + 2 (1/2)
= (3/2)x + 2(1/2)
= (3/2)x + 2 (1/2)
Therefore, the final answer is (3/2)x + 2 (1/2).
1/2 (x + 4) + 1/4 (4x + 2)
= (1/2)x + 2 + (1/4)(4x) + (1/4)(2)
= (1/2)x + 2 + 4/4x + 2/4
= (1/2)x + 2 + x + 1/2
= (1/2)x + x + 2 + 1/2
To add the fractions, we need a common denominator. Multiply 2 by 2/2:
= (1/2)x + (2/2)x + 2 + 1/2
= (1/2)x + (2/2)x + 2 + 1/2
= (1/2 + 2/2)x + 2 + 1/2
= (3/2)x + 2 + 1/2
Now, we can write the answer in mixed number form:
= (3/2)x + 2 + 1/2
= (3/2)x + 2 + 1/2
= (3/2)x + 2 (1/2)
= (3/2)x + 2(1/2)
= (3/2)x + 2 (1/2)
Therefore, the final answer is (3/2)x + 2 (1/2).
(3/2)x + 2 (1/2).
To simplify the expression (3/2)x + 2 (1/2), we can convert the mixed number 2 (1/2) into an improper fraction:
2 (1/2) = 2 + 1/2 = 2/1 + 1/2 = 4/2 + 1/2 = 5/2
Now, we can rewrite the expression:
(3/2)x + 2 (1/2) = (3/2)x + (5/2)
To add these fractions, we need a common denominator of 2. Multiply (3/2)x by 2/2:
(3/2)x + (5/2) = (3/2)x * (2/2) + (5/2)
= (6/4)x + (5/2)
Now, let's combine the terms:
= (6/4)x + (5/2)
To simplify further, we can simplify the with a common factor:
= (3/2)x + (5/2)
Therefore, the answer is (3/2)x + (5/2).
2 (1/2) = 2 + 1/2 = 2/1 + 1/2 = 4/2 + 1/2 = 5/2
Now, we can rewrite the expression:
(3/2)x + 2 (1/2) = (3/2)x + (5/2)
To add these fractions, we need a common denominator of 2. Multiply (3/2)x by 2/2:
(3/2)x + (5/2) = (3/2)x * (2/2) + (5/2)
= (6/4)x + (5/2)
Now, let's combine the terms:
= (6/4)x + (5/2)
To simplify further, we can simplify the with a common factor:
= (3/2)x + (5/2)
Therefore, the answer is (3/2)x + (5/2).
(3/2)x + (5/2).
The expression (3/2)x + (5/2) is already simplified. Therefore, the answer is (3/2)x + (5/2).
what is the sum of (3/2)x + (5/2).
The sum of (3/2)x + (5/2) is (3/2)x + (5/2). Since the two terms have different variables (x and a constant), they cannot be combined further. Thus, the sum is simply (3/2)x + (5/2).
(4d - 3) + (12d + 4)
To solve the expression (4d - 3) + (12d + 4), we'll start by removing the parentheses and combining like terms:
(4d - 3) + (12d + 4)
= 4d - 3 + 12d + 4
Now we can combine the terms with the same variable:
= (4d + 12d) + (-3 + 4)
= 16d + 1
Therefore, the sum is 16d + 1.
(4d - 3) + (12d + 4)
= 4d - 3 + 12d + 4
Now we can combine the terms with the same variable:
= (4d + 12d) + (-3 + 4)
= 16d + 1
Therefore, the sum is 16d + 1.
(2m - 3) + (3n - 1) + (3m +1)
To solve the expression (2m - 3) + (3n - 1) + (3m + 1), we'll start by removing the parentheses and combining like terms:
(2m - 3) + (3n - 1) + (3m + 1)
= 2m - 3 + 3n - 1 + 3m + 1
Pull out like terms:
= (2m + 3m) + (3n) + (-3 - 1 + 1)
= 5m + 3n - 3
Therefore, the sum is 5m + 3n - 3.
(2m - 3) + (3n - 1) + (3m + 1)
= 2m - 3 + 3n - 1 + 3m + 1
Pull out like terms:
= (2m + 3m) + (3n) + (-3 - 1 + 1)
= 5m + 3n - 3
Therefore, the sum is 5m + 3n - 3.
2 (10b + 4) - (b - 2)
To solve the expression 2(10b + 4) - (b - 2), we'll start by distributing the 2 and the negative sign:
2(10b + 4) - (b - 2)
= 20b + 8 - b + 2
Next, we combine like terms:
= 20b - b + 8 + 2
= 19b + 10
Therefore, the value of the expression is 19b + 10.
2(10b + 4) - (b - 2)
= 20b + 8 - b + 2
Next, we combine like terms:
= 20b - b + 8 + 2
= 19b + 10
Therefore, the value of the expression is 19b + 10.
(3g - 4) - 2 (3g + 4)
To solve the expression (3g - 4) - 2(3g + 4), we'll start by distributing the negative 2:
(3g - 4) - 2(3g + 4)
= 3g - 4 - 2(3g) - 2(4)
= 3g - 4 - 6g - 8
Next, we combine like terms:
= (3g - 6g) + (-4 - 8)
= -3g - 12
Therefore, the simplified expression is -3g - 12.
(3g - 4) - 2(3g + 4)
= 3g - 4 - 2(3g) - 2(4)
= 3g - 4 - 6g - 8
Next, we combine like terms:
= (3g - 6g) + (-4 - 8)
= -3g - 12
Therefore, the simplified expression is -3g - 12.